Pertimbangan Antara Mudarat dan Manfaat Dalam Penggunaan Produk Kecantikan - Raihan Mohd Isa; Fatin Nur Majdina Nordin; Saadan Man; Noor Naemah Abdul Rahma (USIM Press, 2024)
VOL. 28 NO. 2 Page (123-153)